THE GEOLOGICAL STRUCTURE OF THE ANTARCTIC PENINSULA AND ALEXANDER I LAND - Grikurov,G. R. (1968)
As a result of the research carried out new material was obtained on the geology of this region which joins South America with the Antarctic continent and which is of interest both from the geographical and geological point of view. (Author) Trans. of Sovetskaya Antarkticheskaya Ekspeditsiya. Informatsionnyi Byulleten (USSR) n58 p13-9 1966.